Dynamic Plastic Behaviour of Overhanging Circular Plate with Various Support Conditions - Zhao Ya-Pu; Yu T.X.; J. Fang (Engineering Transactions)
This paper considers the problem of dynamic plastic response of a rigid, perfectly plastic circular plate with overhang subjected to rectangular pressure pulse. The complete analytical solution is obtained by using the yield condition of Tresca. This problem is of particular interest because it contains the simply supported and the built-in circular plates as two limiting cases, and is likely to represent mare accurately real support conditions occurring in practice. This tl1eory may be considered as a general approach to the problem of a circular plate satisfying various boundary conditions and subjected to dynamic pressure.